PHOTOCONDUCTIVITY OF POLYMER FILM COMPOSITES WITH PARTICLES OF CU(II)/MO(VI) COMPLEXES BASED ON THE STRANDBERG ANION: UDC: 541.14; 541.49; 541.64; 535.015 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
The novel photosensitive polymeric film composites based on non-photoconducting polyvinyl butyral with heterometallic Cu(II)/Mo(VI) compounds have been obtained. The complexes (NH4)2n{[Cu(en)2][Cu(en)(H2O)][P2Mo5O23]}n·3nH2O (1) and (NH4)4n{[Cu(en)(H2O)][P2Mo5O23]}n·3.5nH2O (2) are constructed from Strandberg [P2Mo5O23]6– anions linked through copper-ethylenediamine subunits. Both compounds possess similar polymeric structure with close metal-metal distances (Cu–Cu, Cu–Mo and Mo–Mo), but different chain rigidity. The structure of 1 has a same 1D chain as in the case of 2 with the exception of additional bridging fragments [Cu(en)2] providing extra connectivity between the neighbouring Strandberg anions. Photoconducting properties of the composites under illumination by light from the complex absorption region have been studied. It was shown, that despite similar composition and structure of the complexes, there are different saturation and relaxation time of photoresponse as well as different activation energy. It can be explained by the influence of chain flexibility on transport of non-equilibrium charge carriers. Thus, decreasing of the chain rigidity leads to increasing of photocurrent and decreasing of activation energy by reason of more favorable conditions for charge carriers transport in the particles of the heterometallic coordination compounds.
Keywords: polymeric film composites; heterometallic complexes; photoconductivity; charge carriers transport